Deteksi Dini dan Penguatan Literasi Siswa Sekolah Dasar - Hafidz Triantoro Aji Pratomo; Windiarti Dwi Purnaningrum (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: language skills is essential processing that require in the learning processing. The students use language ability to listening, speaking, reading, and writing. Difficulty in the language skills may affects the academic achievement. The teacher needs to know how to do early detection learning difficulty. Awareness of language disorders and their correlation is important. The aims of this activity to increase teacher knowledge about language and learning difficulty. Also how to give basic activity to improve language and learning process. Methods: Mini seminar and mini workshop was used. Results: The teacher have a good knowledge about language and learning difficulty. Conclusion: This activity is effective to increase teacher awareness about language and learning process.